TINDAK TUTUR ILOKUSI DIREKTIF DALAM DIALOG FILM BOLEHKAH SEKALI SAJA KUMENANGIS KARYA REKA WIJAYA - Ainnun Iza Arnia; Etin Pujihastuti; Nur Indah Sholikhati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze directive illocutionary speech acts in the dialogue of the film Bolehkah Sekali Saja Kumenangis by Reka Wijaya. The method used is a qualitative descriptive approach. The data source of this study is the film Bolehkah Sekali Saja Kumenangis. The data in this study are the utterances of the characters in the dialogue of the film Bolehkah Sekali Saja Kumenangis. Data were collected using the listening method with the basic technique, namely the tapping technique and continued with the advanced technique of free listening and note-taking techniques. Data analysis was carried out using the pragmatic matching method. The results of the study show that the dialogue of this film contains six types of directive illocutionary speech acts, namely prohibitions, requests, advice, criticism, orders, and invitations. This study is recommended as a reference in pragmatic studies, especially the analysis of speech acts in films, and can be further developed by examining other types of illocutionary speech acts.